New Lightning‐Derived Vertical Total Electron Content Data Provide Unique Global Ionospheric Measurements - Erin H. Lay; Jeffery D. Tippmann; Kyle C. Wiens; Sarah E. McDonald; Anthony J. Mannucci; Xiaoqing Pi; Anthea Coster; R. Marc Kippen; Michael J. Peterson; Rob Redmon (Space Weather)
Abstract A newly released, novel ionospheric data set of global gridded vertical total electron content (VTEC) is introduced in this paper. This VTEC data set, provided by Los Alamos National Laboratory (LANL), is derived from very high frequency (VHF; defined as 30–300 MHz) broadband radio‐frequency (RF) measurements of lightning made by U.S. Department of Defense sensing systems on board Global Positioning System (GPS) satellites. This paper presents the new data set (LANL VTEC), discusses the errors inherent in VHF TEC estimation due to ionospheric dispersion, and compares the LANL VTEC to two community standard VTEC gridded products: Jet Propulsion Laboratory's Global Ionospheric Model (JPL GIM) and the CEDAR community's Open Madrigal VTEC gridded measurements of L‐band GNSS (global navigation satellite systems) TEC. We find that the LANL VTEC data have an offset of 3 TECU from CEDAR Madrigal GNSS VTEC and a full‐width‐half‐maximum (FWHM) of 6 TECU. In comparison, the offset between LANL VTEC and the JPL GIM model is −3 TECU, but with a FWHM of 5 TECU. We also compare to Jason‐3 VTEC measurements over the ocean, finding an offset of less than 0.5 TECU and an FWHM of <5 TECU. Because this technique uses a completely different methodology to determine TEC, the sources of errors are distinct from the typical ground‐based GNSS L‐band (GHz) TEC measurements. Also, because it is derived from RF lightning signals, this data set provides measurements in regions that are not well covered by ground‐based GPS measurements, such as over oceans and over central Africa.